Long-Term Impact of Arteriovenous Fistula Ligation on Cardiac Structure and Function in Kidney Transplant Recipients: A 5-Year Follow-Up Observational Cohort Study. Issue 7 (29th July 2021) - Salehi, Tania; Montarello, Nicholas J.; Juneja, Nishant; Stokes, Michael B.; Scherer, Daniel J.; Williams, Kerry F.; King, David; Macaulay, Ewan; Russell, Christine H.; Olakkengil, Santosh A.; Carroll, Robert P.; Faull, Randall J.; et al.
Visual Abstract: Abstract: Key Points: Long-term follow-up of patients undergoing AVF ligation postkidney transplantation demonstrates continuing regression of LVM and LVH. There was no demonstrated negative effect of AVF ligation on long-term kidney allograft function reflected by stability of serum creatinine. There was no observed increase in mortality, nonfatal MI, or cardiac hospitalization in the AVF ligation cohort over the 5-year follow-up period. Background: The long-term effects of arteriovenous fistula (AVF) ligation on cardiovascular structure following kidney transplantation remain uncertain. A prospective randomized, controlled trial (RCT) examined the effect of AVF ligation at 6 months on cardiovascular magnetic resonance imaging (CMR)–derived parameters in 27 kidney transplant recipients compared with 27 controls. A mean decrease in left ventricular mass (LVM) of 22.1 g (95% CI, 15.0 to 29.1) was observed compared with an increase of 1.2 g (95% CI, −4.8 to 7.2) in the control group ( P <0.001). We conducted a long-term follow-up observational cohort study in the treated cohort to determine the evolution of CMR-derived parameters compared with those documented at 6 months post-AVF ligation. Methods: We performed CMR at long-term follow-up in the AVF ligation observational cohort from our original RCT published in 2019. Results were compared with CMR at 6 months postintervention. The coprimary end point was the change in CMR-derived LVM and LVM index at long-term follow-up from imaging at 6 months postindex procedure. Results: At a median of 5.1 years (interquartile range, 4.7–5.5 years), 17 patients in the AVF ligation group were studied with repeat CMR with a median duration to follow-up imaging of 5.1 years (IQR, 4.7–5.5 years). Statistically significant further reductions in LVM (−17.6±23.0 g, P =0.006) and LVM index (−10.0±13.0 g/m 2, P =0.006) were documented. Conclusions: The benefit of AVF ligation on LVM and LVM index regression appears to persist long term. This has the potential to lead to a significant reduction in cardiovascular mortality.